2020
DOI: 10.1177/0268355520951697
|View full text |Cite
|
Sign up to set email alerts
|

A randomized clinical trial of the effects of saphenous and perforating veins radiofrequency ablation on venous ulcer healing (VUERT trial)

Abstract: Objectives To investigate whether radiofrequency endovenous ablation (RFA) of saphenous and perforating veins increases venous leg ulcer (VLU) healing rates and prevents ulcer recurrence. Method This prospective, open-label, randomized, controlled, single-center trial recruited 56 patients with VLU divided into: compression alone (CR, N = 29) and RFA plus compression (RF, N = 27). Primary endpoints were ulcer recurrence rate at 12 months; and ulcer healing rates at 6, 12, and 24 weeks. Secondary endpoints were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 29 publications
1
1
0
1
Order By: Relevance
“…The results of their study showed venous ulcer healing rates had been higher in patients whom received endovenous radiofrequency ablation and two-layer compression bandages when compared with patients whom only received compression bandages alone. Similar results were achieved recently in VUERT Trial 23 with combination of radiofrequency ablation and compression bandages in means of not only venous ulcer treatment but also prevention of recurrences. In addition, the efficacy of cyanoacrylate glue ablation 24 and mechanochemical ablation methods 25 has also been presented in the literature.…”
Section: Discussionsupporting
confidence: 87%
“…The results of their study showed venous ulcer healing rates had been higher in patients whom received endovenous radiofrequency ablation and two-layer compression bandages when compared with patients whom only received compression bandages alone. Similar results were achieved recently in VUERT Trial 23 with combination of radiofrequency ablation and compression bandages in means of not only venous ulcer treatment but also prevention of recurrences. In addition, the efficacy of cyanoacrylate glue ablation 24 and mechanochemical ablation methods 25 has also been presented in the literature.…”
Section: Discussionsupporting
confidence: 87%
“…Currently, there is no clear consensus on how many times a patient with a VLU should visit a vascular outpatient J o u r n a l P r e -p r o o f 10 clinic. Based on other studies, most vascular clinics seem to prefer a single-treatment approach 14,15 . However, other studies support that patients with VLUs should be controlled and treated with further endovenous ablation when necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Die schon zitierte Serie von Lawrence et al [15] beschreibt ausschließlich PV mit hartnäckigen Ulzerationen und kommt zu dem Schluss, dass kein Ulkus ohne den erfolgreichen Verschluss zumindest einer inkompetenten Perforansvene zur Abheilung gelangte. In der VUERT-Studie konnte in 56 Fällen ein statistisch rascheres Abheilen der Ulzerationen nach erfolgreicher endovenöser Therapie der PV festgestellt werden (p < 0,05) [18].…”
Section: Diskussionunclassified